2018
DOI: 10.3390/jcm7120484
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cardiovascular Risk and Diabetes with Colorectal Neoplasia: A Site-Specific Analysis

Abstract: Several studies have shown site-specific differences in colorectal cancer (CRC) with respect to the risk factors. CRC was shown to be associated with cardiovascular risk (CVR) factors, but site-specific variations have not been investigated so far. This study aimed to assess the associations between the prevalence and subsite-specific differences of colorectal neoplasia and established CVR scores or known coronary artery disease (CAD) in a large asymptomatic European screening cohort (N = 2098). Participants u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 71 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…As previously described, participants were examined on 2 consecutive days ( 10 ), including ultrasound ± transient elastography and laboratory characterization including Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) and an oral glucose tolerance test (OGTT). In addition, participants completed a questionnaire about lifestyle and dietary habits.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, participants were examined on 2 consecutive days ( 10 ), including ultrasound ± transient elastography and laboratory characterization including Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) and an oral glucose tolerance test (OGTT). In addition, participants completed a questionnaire about lifestyle and dietary habits.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-four records were excluded due to the inclusion and exclusion criteria. Finally, a total of 12 studies [28][29][30][31][32][33][38][39][40][41][42][43] including one study which was identified through cross-references were included. The detailed information of the selection process was presented in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…All studies explored the role of CVD risk assessment method on the detection of AD, and some of them also focused on colorectal high risk adenoma 30,32 and AN. 28,29,38,42,43 Creative Commons license and disclaimer available from: http://creativecommons.org/licenses/by/4.0/legalcode. 36 Abbreviations: CVD, cardiovascular disease; CRN, colorectal neoplasia.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyrate is critical for intestinal microbial balance and colon health and the atrophy of butyrate metabolism was associated with the pathogenesis of various colonic diseases [83]. The association of Tyzzerella 4 from the Lachnospiraceae family with CRC can be due to its increased occurrence in patients with higher cardiovascular risk (CVR) factor scores [84], that are associated also with CRC [85]. Presence of Massilia in CRC patients was also never described previously, but it was detected in patients with pancreatic cancer [86].…”
Section: Tumour Crc Microbial Subtypesmentioning
confidence: 99%